Hydrogen Peroxide Production is a General Property of the Lignifying Xylem from Vascular Plants - BARCELÓ, A. R. O. S. (Annals of Botany, 1998)
Production of hydrogen peroxide (H2O2) by the lignifying xylem of several vascular plants has been studied using a new histochemical method based on the H2O2-dependent oxidation of 3,5,3′5′-tetramethylbenzidine (TMB) catalysed by cell wall peroxidases. This method allows H2O2to be determined in the range of 5–100 μm, where other methods, such as the KI/starch reagent, fail. With this method, it has been possible to determine H2O2production in the lignifying xylem of a wide range of vascular plants (gymnosperms and angiosperms). The capability of xylem tissues of sustaining H2O2production lends support to the hypothesis that cinnamyl alcohol polymerization in xylem vessels is caused by an H2O2-dependent oxidative coupling process.Copyright 1998 Annals of Botany Company
10.1006/anbo.1998.065510.1006/anbo.1998.0655
Keywords: H2O2 generation; lignification; peroxidase; tetramethylbenzidine; Xylem

Hydrogen Peroxide Production is a General Property of the Lignifying Xylem from Vascular Plants - BARCELÓ, A R O S (Annals of Botany, 1998)
Production of hydrogen peroxide (H2O2) by the lignifying xylem of several vascular plants has been studied using a new histochemical method based on the H2O2-dependent oxidation of 3,5,3′5′-tetramethylbenzidine (TMB) catalysed by cell wall peroxidases. This method allows H2O2to be determined in the range of 5–100 μm, where other methods, such as the KI/starch reagent, fail. With this method, it has been possible to determine H2O2production in the lignifying xylem of a wide range of vascular plants (gymnosperms and angiosperms). The capability of xylem tissues of sustaining H2O2production lends support to the hypothesis that cinnamyl alcohol polymerization in xylem vessels is caused by an H2O2-dependent oxidative coupling process.Copyright 1998 Annals of Botany Company
10.1006/anbo.1998.0655
Keywords: H2O2 generation; lignification; peroxidase; tetramethylbenzidine; Xylem